Persepsi Mahasiswa Akuntansi dan Alumni Program Studi Akuntansi Politeknik Negeri Batam yang Telah Bekerja Terhadap Etika Bisnis - Ime Iranovita Simanjuntak; Sinarti Sinarti (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2013)
Ethics is a moral principle and the Act became a grounding measurement someone so what he does is viewed by the public as a commendable Act and enhance the dignity and honor of a person. This research aims to examine and provide empirical evidence about the difference of perception between the accounting student who was still sitting on the bench and associated with the accounting student alumni have been working against business ethics. The population of this research are students majoring in accounting year 2012/2013 and all accounting study program alumni at Batam State Polytechnic College. The Data collected by means of questionnaires. Test results suggests that there was no difference in the perception of the business ethics between students alumni who haveworked.